Characterization of extracellular vesicles by capillary zone electrophoresis: A novel concept for characterization of a next-generation drug delivery platform - Aleksandra Steć; Andrea Heinz; Szymon Dziomba (Journal of Pharmaceutical Analysis)
Extracellular vesicles (EVs) are a part of a cell-to-cell communication system of prokaryotic and eukaryotic organisms. Their ability to penetrate biological barriers and to transfer molecules between cells shows their potential as a novel class of drug delivery platform. However, because of the great heterogeneity of EVs and the complexity of biological matrices from which they are typically isolated, reliable quality control procedures need to be established to ensure their safety for medical use. According to current recommendations, quantification of EVs, confirmation of their identity, and purity assessment require the use of several analytical techniques, including particle-size distribution analysis, proteomics, and electron microscopy, making the characterization process demanding. Capillary electrophoresis (CE) has recently emerged as an alternative tool for EV characterization. In this study, the available literature on this novel concept for EV characterization was reviewed. Its performance was critically evaluated and compared with currently used methods. The utility of CE in the quality control of EV-based medicines was discussed.